Cypriot ritual and cult from the Bronze to the Iron Age: a longue-durée approach - Papantoniou, Giorgos (Journal of Greek Archaeology, 2016)
In two recent studies on Early Iron Age Cypriot sanctuaries and religion—the first dedicated to the memory of John N. Coldstream, the second to the memory of James R.B. Stewart—I attempted to show that looking at Cypriot ritual places (and practices) ‘before and after’ can be a stimulating and valuable methodological tool for understanding Cypriot ritual and cult diachronically. A drastic transformation imprinted upon the physical and socio-political landscape of the island during the Early Iron Age relates to the establishment—for the first time in the history of the island—of the extra-urban temenos sanctuary, related to the territorial formation of the Cypriot polities. After a careful analysis of Early Iron Age sacred topography and material culture assemblages, the next step would be a meticulous examination of their associated rituals, cults, and iconography in order to illustrate better the transplantation and transformation of Late Cypriot ideas (and ideals) into the Iron Age.